First case of scrub typhus with meningoencephalitis from Kerala: An emerging infectious threat - Saifudheen, K. (Medknow Publications & Media Pvt Ltd, 2012)
Scrub typhus is a rickettsial disease caused by Orientia tsutsugamushi, one of the most common infectious diseases in the Asia-Pacific region. It has been reported from northern, eastern, and southern India, and its presence has been documented in at least 11 Indian states. However, scrub typhus meningoencephalitis has not been well documented in Kerala. We report two cases of scrub typhus meningoencephalitis from northern Kerala. The diagnosis was made based on the clinical pictures, presence of eschar, and a positive Weil–Felix test with a titer of > 1:320. The first patient succumbed to illness due to respiratory failure and the second patient improved well.